Phenotypic expression of Hashimoto’s thyroiditis is absolutely atypical in girls with Turner syndrome - Salzano, Giuseppina; Calafiore, Mariarosa; Mignosa, Cristina; Passanisi, Stefano; Trombatore, Jessica; Zirilli, Giuseppina (Acta Biomedica Atenei Parmensis, 2016)
Background: It is unknown whether phenotypic expression of Hashimoto’s thyroiditis (HT) might be conditioned by the association with Turner syndrome (TS). Objectives: To focus on the most recent pediatric studies concerning epidemiology and biochemical course of HT in TS girls. Design: The epidemiological peculiarities of TS-related HT in pediatric age were compared with those usually observed in non-TS girls with HT and results are summarized in Tables 1 and 2. Conclusions: 1) phenotypical expression of HT in TS girls is significantly different from that observed in girls without TS; 2) such differences concern the epidemiological picture, the biochemical presentation modes and also the natural history from HT diagnosis onwards; 3) these peculiarities of TS-related HT are not necessarily linked with a specific karyotype.